2021
DOI: 10.1080/1744666x.2021.1899811
|View full text |Cite
|
Sign up to set email alerts
|

Palindromic rheumatism: a unique and enigmatic entity with a complex relationship with rheumatoid arthritis

Abstract: Introduction: Palindromic rheumatism (PR) is a form of relapsing/remitting arthritis that may evolve to chronic rheumatic disease, mainly rheumatoid arthritis (RA). The exact nature of PR is unclear, as it may be considered a disease in itself, an abortive form of RA or just a pre-RA stage. Areas covered:The authors review the most relevant epidemiological and clinical aspects of PR, especially the pathogenetic role of autoimmunity in PR, with most patients having a characteristic autoantibody profile similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 61 publications
0
21
1
5
Order By: Relevance
“…PR has immunogenetic, clinical and serological associations with rheumatoid arthritis (RA) and may progress into chronic diseases, mainly RA 2,3 . It has been reported that PR progresses to RA in 10%‐66% of cases, mainly within 10 years of the onset of the disease 2‐4 . Although various studies show that treatment with disease‐modifying antirheumatic drugs (DMARDs) can control attacks of PR and prevent or postpone progression of disease to RA, no controlled studies have been performed about the efficacy of various DMARDs on the treatment of PR and there is no guideline for the treatment of PR 5 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PR has immunogenetic, clinical and serological associations with rheumatoid arthritis (RA) and may progress into chronic diseases, mainly RA 2,3 . It has been reported that PR progresses to RA in 10%‐66% of cases, mainly within 10 years of the onset of the disease 2‐4 . Although various studies show that treatment with disease‐modifying antirheumatic drugs (DMARDs) can control attacks of PR and prevent or postpone progression of disease to RA, no controlled studies have been performed about the efficacy of various DMARDs on the treatment of PR and there is no guideline for the treatment of PR 5 .…”
Section: Introductionmentioning
confidence: 99%
“…1 PR has immunogenetic, clinical and serological associations with rheumatoid arthritis (RA) and may progress into chronic diseases, mainly RA. 2,3 It has been reported that PR progresses to RA in 10%-66% of cases, mainly within 10 years of the onset of the disease. [2][3][4]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…20 The presence of autoantibodies in most patients with PR and the evolution of the disease to RA in a significant number of patients introduced a prominent role of autoimmunity in the pathogenesis of PR. [1][2][3] However, the relapsing remitting course of the disease and the higher frequency of MEFV gene mutation have raised the role of inflammasome-related mechanisms in the pathogenesis of PR, giving it the appearance of an autoinflammatory disease. 1,20,21 The main mechanism of action of leflunomide in RA and other autoimmune diseases is inhibition of lymphocytes proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…1 The role of systemic autoimmunity in the pathogenesis of PR has been suggested due to the presence of autoantibodies including rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPAs) in most patients and the disease evolution to rheumatoid arthritis (RA) in 10%-65% of patients. [1][2][3] The goal of treatment in PR is to control the attacks and prevent disease evolution to chronic arthritis. 1 Treatment options for PR are limited and there is no guideline for treatment.…”
mentioning
confidence: 99%